Quantification of Daily-Living Gait Quantity and Quality Using a Wrist-Worn Accelerometer in Huntington's Disease - Keren, Karin; Busse, Monica; Fritz, Nora E.; Muratori, Lisa M.; Gazit, Eran; Hillel, Inbar; Scheinowitz, Micky; Gurevich, Tanya; Inbar, Noit; Omer, Nurit; Hausdorff, Jeffrey M.; Quinn, Lori (Frontiers in Neurology, 2021)
Background: Huntington’s disease (HD) leads to altered gait patterns and reduced daily-living physical activity. Accurate measurement of daily-living walking that takes into account involuntary movements (e.g. chorea) is needed. Objective: To evaluate everyday gait quantity and quality in HD, taking into account irregular movements. Methods: 29 HD participants and 21 healthy age-matched controls completed clinic-based assessments and a standardized laboratory-based circuit of functional activities, wearing tri-axial accelerometers on the wrists, legs, and trunk. Subsequently, participants wore a tri-axial accelerometer on their non-dominant wrist for 7 days. Gait measures included quantity (e.g., steps per day) and quality (e.g., regularity) metrics, and percentage of walking bouts with irregular movements. Results: Measures of daily-living gait quantity including step counts, walking time and bouts per day were similar in HD participants and healthy controls (p>0.05). HD participants with higher clinician-rated upper body chorea had a greater percentage of walking bouts with irregular movements compared to those with lower chorea (p=0.060) and healthy controls (p<0.001). Even after accounting for irregular movements, within-bout walking consistency was lower in the HD participants compared to controls (p<0.001), while across-bout variability of these measures was higher (p<0.001). Many of the daily-living measures were associated with disease-specific measures of motor function. Conclusions: These results suggest that a wrist-worn accelerometer can be used to evaluate the quantity and quality of daily-living gait in people with HD, while accounting for the influence of irregular (choreic-like) movements, and that gait features related to within- and across-bout consistency markedly differ in HD and controls.